Common Hematological Abnormalities in patients with Malaria presenting at Saidu Teaching Hospital, Swat Pakistan - Abdul Ahad, Saima Qadir, Aleem ur Rashid, Amir Zeb Swati (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the frequency of common hematological abnormalities in patients with malaria. Study Design: A cross-sectional study. Place and Duration of the Study: Department of Medicine, Saidu Teaching Hospital, Swat Pakistan from November 2019 to May 2020. Material and Methods: A total of 137 patients of both genders aged between 18-60 years and who presented with malaria in emergency or outpatient department were analyzed. Ten cc blood was taken from all enrolled patients and sent to institutional laboratory for the detection of anemia, thrombocytopenia, leucopenia and disseminated intravascular coagulation (DIC). Frequency of common hematological abnormalities among patients of malaria was noted. For data analysis, SPSS version 26.0 was used. Results: In a total of 137 patients, 95 (69.3%) were male and 42 (30.7%) female. Overall, mean age was 29.2±13.18 while 84 (61.3%) patients were aged between 18 to 30 years. Mean duration of disease was 1.2±1.09 weeks while 89 (65.0%) patients had duration of disease <1 week. Table-1 is showing baseline characteristics of all patients. Anemia was found in 121(88.3%) patients, thrombocytopenia in 67(48.9%), leucopenia in 20 (14.6%) and 35 (25.5%) had DIC. Conclusion: The frequency of hematological abnormalities in patients with malaria was high. Anemia was found in 88.3% malaria cases, thrombocytopenia 48.9%, leukopenia 14.6% and DIC 25.5%.